2018
DOI: 10.21859/jech.5.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy of Employees of Hamadan University of Medical Sciences and Related Demographic Factors

Abstract: Background and Objective: One of the important determinants of health in every society is health literacy. The present study was conducted to determine health literacy status of employees of Hamadan University of Medical Sciences and related factors. Materials and Methods: This cross-sectional study was performed in 2016 among 188 employees in Hamadan University of Medical Sciences. The participants were selected through the stratified sampling method. The data collection instrument was Health Literacy for Ira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…These results are consistent with the results of Panahi et al [32]. Also, in the studies of Panahi et al [33], Glory et al [34], and Ansari et al [35] understanding had the highest mean score among health literacy skills. Moreover, these results are consistent with the results of the study of Mahmoudi and Taheri [36] in which access had the highest mean score.…”
Section: Resultssupporting
confidence: 91%
“…These results are consistent with the results of Panahi et al [32]. Also, in the studies of Panahi et al [33], Glory et al [34], and Ansari et al [35] understanding had the highest mean score among health literacy skills. Moreover, these results are consistent with the results of the study of Mahmoudi and Taheri [36] in which access had the highest mean score.…”
Section: Resultssupporting
confidence: 91%
“…These results were consistent with the results of Panahi et al [24]. Panahi et al [34], Khoshravesh et al [35] and Ansari et al [36] reported the highest average health literacy score for comprehension skill, which was in line with our ndings. Also, these results are consistent with the results of Mahmoudi and Taheri's study [37], in which the highest average score was for access skill.…”
Section: Discussionsupporting
confidence: 94%
“…Employed participants had a significantly lower level of COVID-19 VL in comparison with unemployed participants, which is in opposition to previous research [ 22 ]. However, Khoshravesh et al [ 23 ] also reported about the borderline level of health literacy of employed people in Iran. Other authors also point out that employment is a significant factor in the level of health literacy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%